Osteopathic Manipulation Treatment on postural balance: a systematic review. - Veloso, Carolina Fantinel; Silveira, Aron Ferreira da; Garcia, Michele Vargas; Romero, Caio Alexandre Parra (Manual Therapy, Posturology & Rehabilitation Journal, 2016)
Introduction: The postural balance is achieved through the interaction between the visual, proprioceptive and vestibular systems. Osteopathic manipulation treatment may interact with these systems through neural or sensory facilitation and consequently, restore or optimize the postural balance. Objective: Find and analyze studies that evaluated the effects of osteopathic manipulation in the balance of individuals. Methods: systematic review using the health descriptors (DeCS) “osteopathic manipulation treatment” and “postural balance”, posting articles between 2009 and 2015 in different countries, in SciELO, LILACS and PubMed databases, to respond to the objective of study. Results: it included six scientific articles, of different nationalities, who used various maneuvers osteopathic manipulation in the treatment of postural balance, measured by force platform (2 studies), baropodometry (2 studies), functional questionnaire DHI (1 item) and computerized dynamic posturography (1 article) Conclusion: The osteopathic manipulation is effective in the treatment of postural balance in all studies included in the review.